Adolescent Bullying and Sleep Difficulties - Simon C. Hunter; Kevin Durkin; James M. E. Boyle; Josephine N. Booth; Susan Rasmussen (Europe's Journal of Psychology, 2014)
This study evaluated whether adolescents who report having been bullied, being bullies, or report both being a bully and being bullied experience more sleep difficulties than children uninvolved in bullying. The study drew upon cognitive theories of insomnia, investigating whether the extent to which young people report worrying about bullying can moderate associations between victimization and sleep difficulties. Participants were 5420 adolescents who completed a self-report questionnaire. Pure Victims (OR = 1.72, 95% CI [1.07, 2.75]), Pure Bullies (OR = 1.80, 95% CI [1.16, 2.81]), and Bully-Victims (OR = 2.90, 95% CI [1.17, 4.92]) were all more likely to experience sleep difficulties when compared to uninvolved young people. The extent to which young people reported worrying about being bullied did not moderate the links between victimization and sleep difficulties. In this way, bullying is clearly related to sleep difficulties among adolescents but the conceptual reach of the cognitive model of insomnia in this domain is questioned.